The study of public sphere and communicative action on Telegram: Applying Habermas' notions on Iranian journalists conversations - hadi khaniki; Hossein Kermani (مطالعات رسانه‌های نوین, 2019)
Alongside with the advent and proliferation of internet usage in societies, more debates on the potentials of internet in reviving or reshaping the public sphere or even creating a new one has aroused. Thus, this paper is trying to evaluate if a micro public sphere is shaped in a Telegram group where Iranian journalist had discussed the requirements and conditions for establishing a professional association. Telegram is the most popular Instant Messaging Application in Iran now, and its groups provide a very convenient space for discussions and conversations. That is why numerous groups are created to enable people to participate in public and (potentially) free discussions. In September 2016, when some Iranian journalist tried to establish a professional association for Tehran-based journalists, a group in Telegram was created which attracted more than 600 members at that time. The announced purpose of the group was exploring the circumstances and providing helpful suggestions for those working to prepare the statute of the association. Thus, using a triangulation of three methods, we tried to achieve a close reading of messages in the group (we analyzed 1117 messages from the beginning before the theoretical saturation was achieved). We identified 5 different kinds of conversations: simple, empathy, non-challenging, challenging, and hostile. Findings showed that the members’ actions in some cases can be seen as communicative rather than instrumental or strategic. Results also indicated that as debates got more hostile, many of public sphere’s norms were violated.